An observational study to find out changes in arterial oxygen tension during fiberoptic bronchoscopy - Kumar, Pardeep; Purohit, Gopal; Choudhary, C. R.; Borana, Hemant; Shyam, Radhe (International Journal of Advances in Medicine, 2022)
Background: Arterial hypoxaemia is the commonest complication, since respiratory depressant drugs are used for premedication, and the airway is also partially occluded by the bronchoscope. The study is therefore designed to find out the changes in arterial oxygen tension during (FOB) along with effect on central hemodynamics, pre and post procedure ECG and PFT. Objectives were to find out the changes in arterial oxygen tension during FOB, to study the effects of FOB on central hemodynamics, electrocardiographically and pulmonary function tests. Methods: One hundred patients aged above 20 years undergoing FOB were evaluated for the arterial oxygen tension and cardiac rhythm changes at KNCH, Jodhpur during 12 months study period from 2019 to 2020. Results: All patients developed a fall in PaO2 following FOB but hypoxaemia was noted only in 18 cases. Bronchial washing, punch biopsy and brush biopsy did contribute to hypoxaemia significantly. There was a uniform rise in heart rate in all the patients after FOB which was statistically significant. There was slight sinus tachycardia in most of the cases although ECG indicated no major arrhythmias. The pulmonary functions which include change in VC, FVC, FEV1 and PEFR after FOB, on statistically comparison no statistical difference could be observed. There was no significant change in PaCO2 level and pH level. Mean of SBP and mean of DBP was statistically significant. Conclusions: All patients showed a decline in arterial PaO2 after FOB which was highly significant. There was slight sinus tachycardia in most of cases. FOB itself does not endanger the patients with any significant or serious complications.